Feel Good Factory on Beating the Blues - Elisabeth Wilson (Research Press, 2012)
The Feel Good Factory on Beating the Blues contains simple, no-nonsense ideas to help you get out of the doldrums and back to the land of the living. Thirty practical and down-to-earth chapters will set you well on your way to beating the blues. You'll find questionnaires to point you in the right direction, instant 'feel good now' tips that you can put into practice straight away, and helpful question and answer sections. Also discover what well-known people who suffer from depression do to keep it at bay (hey, they pay big money for all that expertise so why not have a go at some of their advice!). With a few minutes a day spent trying some of the techniques in this book you can rediscover the person that you know exists, deep down; the happier, more fulfilled you.